The truth doesn't have to hurt : how to use criticism to strengthen relationships, improve performance, and promote change - Bright, Deborah (AMACOM, American Management Association, 2015)
Ignoring problems or always saying nice things will only maintain the status quo. This research-backed book delivers proven techniques and tools for motivating people and triggering improvement - swiftly and painlessly.